PENGARUH DISIPLIN KERJA, REWARD, DAN TOUR OF DUTY TERHADAP KINERJA ANGGOTA BABEK TNI DENGAN VARIABEL INTERVENING MOTIVASI - Antariksa, Susilo Negoro Dony; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to analyze the impact of work discipline, rewards, and tour of duty on the performance of Babek TNI members with motivation as an intervening variable. A quantitative method with a survey approach was used to collect data from 200 respondents. Data analysis techniques utilized Structural Equation Modeling (SEM). The results indicate that work discipline, rewards, and tour of duty positively and significantly influence motivation, which in turn affects member performance. Work discipline contributes the most, followed by rewards and tour of duty. Motivation is proven to be a mediating variable that strengthens the relationship between independent variables and performance. This study implies the importance of enhancing discipline and providing fair rewards to optimize organizational performance.